Penerapan Digital Marketing Pada UMKM Kopitiam Good Taste Di Batam - Hesniati, Hesniati; Verandi, Rizal (Pakis Journal Institute, 2024)
Kopitiam Good Taste MSMEs is a business engaged in the food and beverage sector. The development of technology is increasingly advanced and everything can be done only using technology where by introducing MSMEs on social media can help MSMEs be more quickly recognized by the wider community around the world and not only in the local city. The purpose of this community service activity is to help MSMEs to innovate and develop their businesses in increasing sales and income through promotions and social media ads held or by having effective digital marketing in order to attract the attention of the wider community. The method used is to use primary data where the data is obtained directly from Kopitiam Good Taste MSME partners and observation activities and direct interviews with MSME owners are carried out by the author to find out the problems that are being experienced. The outputs achieved in this community service activity are in the form of creating a linktree containing some information about Kopitiam Good Taste MSMEs, creating Instagram and Facebook accounts, creating Instagram ads and Facebook ads, making digital posters posted on social media and making various promotional videos and daily activities of Kopitiam Good Taste MSMEs.